If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -4 = 9x + 7 Reorder the terms: -4 + 8x = 9x + 7 Reorder the terms: -4 + 8x = 7 + 9x Solving -4 + 8x = 7 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. -4 + 8x + -9x = 7 + 9x + -9x Combine like terms: 8x + -9x = -1x -4 + -1x = 7 + 9x + -9x Combine like terms: 9x + -9x = 0 -4 + -1x = 7 + 0 -4 + -1x = 7 Add '4' to each side of the equation. -4 + 4 + -1x = 7 + 4 Combine like terms: -4 + 4 = 0 0 + -1x = 7 + 4 -1x = 7 + 4 Combine like terms: 7 + 4 = 11 -1x = 11 Divide each side by '-1'. x = -11 Simplifying x = -11
| 8z-6=7z+16 | | 28x-140=0 | | .6x^2-4x-160=0 | | 8=-3u | | 8z-6=7z+6 | | 4+d=11 | | 48/1=a+7/6 | | 2x^2=-14x-20 | | 5x-10=-9x | | w^2-36=-64 | | 15x-35y+90=0 | | 3(4x-22)=78 | | A^2-8a-9=0 | | 12x^5y^2z^2-24x^4y^2z^2+12x^3y^2z^2= | | 86=29+y | | (x^2+10x)+y^2=0 | | 10-4n=26 | | 56a+90+58a=92 | | x^3-2x=0 | | x-3+x+x+5=33 | | 5+.5s=s | | 4m^2-25= | | 6x+28=10x | | 144b^2=36 | | 56=26x | | 7+x-9=103732 | | x^3+5x^2+4x-20=0 | | x^4+-8x^3+17x^2+-8x+16=0 | | X=7-4+3*0+1 | | 16n^2-9= | | 62=12z+14 | | x^4+-8x^3+17x^2+-8x+1=0 |